The Hero’s journey: Analyze how the concept of the hero's journey is applied in different literary works. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The hero's journey is a well-known narrative structure that has been used in countless literary works throughout history. This research paper explores how the concept of the hero's journey is applied in different literary works, examining the various stages of the journey and how they contribute to the overall narrative. By analyzing a selection of texts from different genres and time periods, this paper aims to demonstrate the universality and enduring appeal of the hero's journey as a storytelling device.This research paper explores the concept of the hero's journey, also known as the monomyth, as a ubiquitous narrative framework. Drawing on the theories of Joseph Campbell, it analyzes how this structure shapes literary works across cultures and genres. The paper delves into the key stages of the hero's journey – the Ordinary World, the Call to Adventure, Tests, Allies and Enemies, the Ordeal, the Reward, the Road Back, the Resurrection, and the Return – and demonstrates their application in diverse literary works. Through in-depth analyses of specific examples from various periods and traditions, the paper illuminates the enduring power of the hero's journey and its ability to resonate with readers on a fundamental level.